2020
DOI: 10.1039/c9cs00607a
|View full text |Cite
|
Sign up to set email alerts
|

A review on fundamentals for designing oxygen evolution electrocatalysts

Abstract: The fundamentals related to the oxygen evolution reaction and catalyst design are summarized and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
1,369
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,925 publications
(1,384 citation statements)
references
References 203 publications
(266 reference statements)
11
1,369
0
4
Order By: Relevance
“…The metal‐oxygen covalency, which is determined by calculating the energy difference between the metal 3d and O 2p band centers, has been widely used as intrinsic factor correlated to the OER performance. [ 2,19,68,77–79 ] Compared to Ni‐OH, the energy difference between Ni 3d and O 2p band centers of NiFe‐LDH is clearly lower (Figure 5b), suggesting that enhanced NiO covalency was obtained in NiFe‐LDH. For R‐NiFe‐CPs, a similar NiO covalency is observed, but an increased Fe‐O covalency was found compared to NiFe‐LDH.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The metal‐oxygen covalency, which is determined by calculating the energy difference between the metal 3d and O 2p band centers, has been widely used as intrinsic factor correlated to the OER performance. [ 2,19,68,77–79 ] Compared to Ni‐OH, the energy difference between Ni 3d and O 2p band centers of NiFe‐LDH is clearly lower (Figure 5b), suggesting that enhanced NiO covalency was obtained in NiFe‐LDH. For R‐NiFe‐CPs, a similar NiO covalency is observed, but an increased Fe‐O covalency was found compared to NiFe‐LDH.…”
Section: Resultsmentioning
confidence: 99%
“…The enhanced metal‐oxygen covalency, which results from synergistic effects between Fe insertion and structural deficiencies, can promote the electron mobility between the metal cations and intermediate anions (e.g., O 2− and O 2 2− ), thereby improving the OER kinetic properties. [ 68,77–79 ]…”
Section: Resultsmentioning
confidence: 99%
“…[34,41] The latest progress in understanding the various mechanisms was recently summarized. [1] Two main scenarios for OER at MCs, following their transformation into oxides, are widely accepted: i) Classical adsorbate evolution mechanism, in which four proton-coupled electron transfer steps occur at the metal center, generating oxygen from the electrolyte, see Figure 2a. [41] In this route, the rate-determining step is often the formation of an OOH intermediate on the metal surface (step 4 in Figure 2a).…”
Section: Structural Properties and Mechanisms Of Oer/orr: Structure Tmentioning
confidence: 99%
“…Among others, water electrolysis, fuel cells and metal-air batteries are promising renewable energy technologies. [1,2] In 2018, approx. 800 MW of fuel cell power was supplied worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…[29] These authors revealed a linear relationship between methane activation energy and oxygen binding energy on the surface (E O ). As oxygen binding energies have been widely applied in predicting the activity of electrocatalysts for oxygen evolution reaction (OER) [73,74] and oxygen reduction reaction (ORR), [73][74][75] the E O descriptor will facilitate the discovery of methane oxidation catalysts based on current OER and ORR catalysts. Indeed, the E O and G f descriptors are intrinsically related, as they both describe the formation energy of surface M−O active sites; it is expected that strong oxygen-binding materials will have low E O and G f and vice versa.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%